Makna Pesan Podcast Suara Berkelas Episode “Cara Menjadi Manusia Disiplin dan Percaya Diri dalam 40 Menit” terhadap Pembentukan Kepercayaan Diri Pendengar - Dastin Abyan Pradipta; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The development of digital technology has changed communication patterns through the presence of podcasts as an educational and motivational medium for listeners. This study aims to determine how listeners interpret messages about discipline and self-confidence, identify key messages that are considered influential, and analyze the role of the Suara Berkelas podcast episode "Cara Menjadi Manusia Disiplin dan Percaya Diri dalam 40 Menit" in building listeners' self-confidence. This study uses a descriptive qualitative approach with a reception analysis method based on Stuart Hall's encoding/decoding framework. Data were collected through semi-structured in-depth interviews with active students of the Vocational School, IPB University, aged 18-25 years who had listened to the entire podcast episode and were selected using a purposive sampling technique. The number of informants was determined based on the principle of data saturation. The results showed that informants interpreted discipline as an internal commitment to remain productive regardless of mood conditions, while self-confidence was interpreted as the courage to start even in imperfect conditions. The motivational messages in the podcast were perceived to be able to encourage informants to reflect on procrastination habits and motivate the emergence of more active actions in making decisions in everyday academic and social life. Based on these findings, listeners positively perceive the Suara Berkelas podcast as a medium that supports the development of discipline and self-confidence through an interpretation process influenced by each informant's personal experiences and circumstances.